Students' Ability in Writing Hortatory Exposition of Eleventh Grade Students at SMAN 14 Pekanbaru - Sri Wahyuni (UIR Press, 2017)
This research represents the descriptive research to describe students’ ability of eleventh grade students at SMAN 14 Pekanbaru in writing hortatory exposition text. The total number of eleventh grade students at SMAN 14 Pekanbaru in academic year 2015/2016 was 210 students that consisted of 7 classes. In this research, the researcher used ‘cluster random sampling technique” to choose the sample, and the total sample of this research amount to 30 students. The data was collected through writing test, where the students were asked to write a hortatory exposition text based on the topics that were provided by researcher of this research. The test was done around 90 minutes for every time of the test. The students’ entire test was scored by two persons as scorers of this research. Those two scores gave scores to the students’ test based on the criteria in the instrumentation of this research. The result showed that the student’ ability in writing hortatory exposition text was categorized “average to good”. It can be proven by the average of students’ writing test score that was 61.65 that cannot achieve the passing grade yet. Key words: Writing Ability, Hortatory Exposition Text